(untitled) (Zaporizhzhia Historical Review, 2021)
The article gives a detailed description of historiography of the Cossack starshyna. Having analyzed the modern level of investigation of this probleme, the author proves the conclusion that creating a fundamental monography „Cossack starshyna of Hetmanship” covering all the activities of Ukrainian elite of those times is one of the most important tasks for modern Ukrainian historians.